Dynamics Analysis of the Transmission System of Front-engine Rear- drive Automobile - Tang Zi; Dong Dawei; Yan Bing; Wang Yuanwen; Fan Dali (Jixie chuandong)
The transmission system of front- engine rear- drive automobile is one of main excitation source of automobile vibration,the vibration of transmission system will seriously affects the NVH performance of the vehicle. Taking the transmission system of a MPV automobile as research object,which has serious car booming noise when operating slowly at a high gear,the source of noise is analyzed by test analysis method,and the simulation method of hypoid gear of main reducer in the system is studied,a rigid- flexible coupled model of transmission containing gear is established and the dynamics analysis is carried out. The result shows,the torsional resonance of transmission excited by alternating torque from engine will impact the meshing force of gear,cause the vibration of car body and make the car booming noise. This mechanism can provide base for the improvement of acoustic characteristic of the automobile.